Long-Term Effects of Residual Chlorine on Pseudomonas aeruginosa in Simulated Drinking Water Fed With Low AOC Medium - Mao, Guannan; Song, Yuhao; Bartlam, Mark; Wang, Yingying (Frontiers in Microbiology, 2018)
Residual chlorine is often required to remain present in public drinking water supplies during distribution to ensure water quality. It is essential to understand how bacteria respond to long-term chlorine exposure, especially with the presence of assimilable organic carbon (AOC). This study aimed to investigate the effects of chlorination on Pseudomonas aeruginosa in low AOC medium by both conventional plating and culture-independent methods including flow cytometry (FCM) and quantitative PCR (qPCR). In a simulated chlorinated system using a bioreactor, membrane damage and DNA damage were measured by FCM fluorescence fingerprint. The results indicated membrane permeability occurred prior to DNA damage in response to chlorination. A regrowth of P. aeruginosa was observed when the free chlorine concentration was below 0.3 mg/L. The bacterial response to long-term exposure to a constant low level of free chlorine (0.3 mg/L) was subsequently studied in detail. Both FCM and qPCR data showed a substantial reduction during initial exposure (0-16 h), followed by a plateau where the cell concentration remained stable (16-76 h), until finally all bacteria were inactivated with subsequent continuous chlorine exposure (76-124 h). The results showed three-stage inactivation kinetics for P. aeruginosa at a low chlorine level with extended exposure time: an initial fast inactivation stage, a relatively stable middle stage, and a final stage with a slower rate than the initial stage. A series of antibiotic resistance tests suggested long-term exposure to low chlorine level led to the selection of antibiotic-resistant P. aeruginosa. The combined results suggest that depletion of residual chlorine in low AOC medium systems could reactivate P. aeruginosa, leading to a possible threat to drinking water safety.